2018
DOI: 10.14260/jemds/2018/873
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Midwives Working in Clinics and Maternity Hospitals in Northwest Iran

Abstract: BACKGROUND Quality of Life is a personal interpretation about the life status in the context of culture and value system. The quality of life of midwives working in the health care system requires special attention. The present study was conducted with an aim to investigate the quality of life of midwives working in clinics and maternity hospitals in northwest of Iran. MATERIALS AND METHODS This cross-sectional study was conducted with participation of 70 midwives working in health centers and maternity hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The results of the present study showed that there is a positive relationship between age and quality of life, so that the quality of life increased with increasing age. This result is consistent with similar studies ( 34 , 35 ), and also is inconsistent with the some studies ( 7 , 36 ). Analysis of regression model showed that age group variable was not significant in model.…”
Section: Discussionsupporting
confidence: 57%
“…The results of the present study showed that there is a positive relationship between age and quality of life, so that the quality of life increased with increasing age. This result is consistent with similar studies ( 34 , 35 ), and also is inconsistent with the some studies ( 7 , 36 ). Analysis of regression model showed that age group variable was not significant in model.…”
Section: Discussionsupporting
confidence: 57%